The state of religious expression in Malaysia - Mohd Sani, Mohd Azizuddin; Abdul Hamed Shah, Dian Diana (2011)
Great care is taken not to impinge on the religious sensitivities of various groups.Given the fact that Islam is the religion of the Federation, care is taken not to publish articles that cast a slur, intended or otherwise, on the religion or its adherents.All the media follow this policy.Thus, religious expression has always been monitored by the government in order to protect the racial harmony in multiracial-multicultural society in Malaysia.This protection is covered in the constitution and it can clearly be seen in practice in certain issues such as religious expression in the press, blasphemy, religious authority, inter-faith commission, and dress codes.Thus, Malaysia is restrictive in dealing with the issue of religious expression.It is quite controversial, even though the purpose is for political stability and security, because the state has been accused of restricting religious expression for regime security and political power.